Covertly active and progressing neurochemical abnormalities in suppressed HIV infection. Issue 1 (January 2018) - Cysique, Lucette A.; Jugé, Lauriane; Gates, Thomas; Tobia, Michael; Moffat, Kirsten; Brew, Bruce J.; Rae, Caroline
Abstract : Objective: To assess whether HIV-related brain injury is progressive in persons with suppressed HIV infection. Methods: Seventy-three HIV+ virally suppressed men and 35 HIV− men, screened for psychiatric and alcohol/drug use disorders, underwent neuropsychological evaluation and proton magnetic resonance spectroscopy ( 1 H-MRS) at baseline and after and 23 ± 5 months. 1 H-MRS included brain regions known to be vulnerable to HIV and aging: frontal white matter (FWM), posterior cingulate cortex (PCC), and caudate area (CA). Major brain metabolites such as creatine (Cr: marker of cellular energy), N -acetyl aspartate (NAA: marker of neuronal integrity), choline (marker of cellular membrane turnover), glutamate/glutamine (excitatory/inhibitory neurotransmitter), and myo -Inositol (mI: marker of neuroinflammation) were calculated with reference to water signal. Neurocognitive decline was corrected for practice effect and baseline HIV-associated neurocognitive disorder (HAND) status. Results: Across the study period, 44% had intact cognition, 42% stable HAND (including the single case that improved), 10% progressing HAND, and 4% incident HAND. When analyzing the neurochemical data per neurocognitive trajectories, we found decreasing PCC Cr in all subgroups compared with controls ( p < 0.002). In addition, relative to the HIV− group, stable HAND showed decreasing FWM Cr, incident HAND showed steep FWM Cr reduction, whereas progressing HAND had a sharply decreasing PCC NAA and reduced but stable CA NAA. When analyzing the neurochemical data at the group level (HIV+ vs HIV− groups), we found stable abnormal metabolite concentrations over the study period: decreased FWM and PCC Cr (both p < 0.001), decreased PCC NAA and CA NAA (both p < 0.05) and PCC mI increase ( p < 0.05). HIV duration and historical HAND had modest effects on metabolite changes. Conclusions: Our study reveals covertly active or progressing HIV-related brain injury in the majority of this virally suppressed cohort, reflecting ongoing neuropathogenic processes that are only partially worsened by historical HAND and HIV duration. Longer-term studies will be important for determining the prognosis of these slowly evolving neurochemical abnormalities.